2016
DOI: 10.1103/physreve.94.062211
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of a time-dependent and dissipative oval billiard: A heat transfer and billiard approach

Abstract: We study some statistical properties for the behavior of the average squared velocity -hence the temperature -for an ensemble of classical particles moving in a billiard whose boundary is time dependent. We assume the collisions of the particles with the boundary of the billiard are inelastic leading the average squared velocity to reach a steady state dynamics for large enough time. The description of the stationary state is made by using two different approaches: (i) heat transfer motivated by the Fourier la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…The explanation of the initial plateau is related to the behavior of the velocity distribution function [17]. For an initial velocity larger than the maximum moving wall velocity, say V max = aǫ, the following is observed: (1) Part of the ensemble of particles acquires energy leading to such portion of the ensemble to grow energy; (2) However, another part of the ensemble leads to decreasing of velocity.…”
mentioning
confidence: 99%
“…The explanation of the initial plateau is related to the behavior of the velocity distribution function [17]. For an initial velocity larger than the maximum moving wall velocity, say V max = aǫ, the following is observed: (1) Part of the ensemble of particles acquires energy leading to such portion of the ensemble to grow energy; (2) However, another part of the ensemble leads to decreasing of velocity.…”
mentioning
confidence: 99%
“…As discussed in Ref. [24], the behavior of the V rms (n) can be summarized as: (i) for short n, V rms (n) ∝ n β ; (ii) for large enough n, it is observed that V sat ∝ (1−γ) α1 (ηǫ) α2 , (iii) finally the crossover iteration number is written as n x ∝ (1 − γ) z1 (ηǫ) z2 . Doing the same procedure we made along on the paper we end up with the following set of critical exponents α 1 = −0.5, z 1 = −1, α 2 = 1, z 2 = 0 and β = 0.5 as earlier obtained in Ref.…”
mentioning
confidence: 94%
“…Doing the same procedure we made along on the paper we end up with the following set of critical exponents α 1 = −0.5, z 1 = −1, α 2 = 1, z 2 = 0 and β = 0.5 as earlier obtained in Ref. [24] by using the thermodynamical approach.…”
mentioning
confidence: 99%
“…In a regular situation, a gas of non-interacting particles with an initial low temperature T 0 will increase its energy if introduced in a, pre-viously empty, recipient with walls at ambient temperature T a > T 0 . The opposite will happen if the gas is at an initially larger temperature T 0 > T a [13]. This thermalization process, in general, manifests as a monotonic change in temperature as time advances, leading to an asymptotic state of thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%